RELIGIOUSLY HORROR: RELIGIOUS ELEMENTS IN PENGABDI SETAN (2017) AND PENGABDI SETAN: COMMUNION (2022) - Rieke Septiana; Alfioni Indi Alifah; Okta Dwi Sulistyowati Setyoningsih; Fitri Rahmawati (Program Studi Komunikasi dan Penyiaran Islam Pascasarjana UIN KHAS Jember, 2024)
This research explores the religious elements in the Indonesian horror movies ‘Pengabdi Setan’ (2017) and Pengabdi Setan: Communion (2022) using a descriptive qualitative approach, guided by Hank Davis and Javor’s religious horror theory (2004). The research explores how both movies incorporate religious elements from Islam and local beliefs to create a compelling horror narrative. Davis and Javor's theory, which examines the relationship between religion and the supernatural in horror, provides a framework for analyzing the moral and existential tensions between faith and evil forces. By focusing on the role of religious elements in shaping character behavior and plot development, the research highlights how these movies reflect broader societal concerns and spiritual struggles. The analysis reveals how religious elements intensify the horror experience, while also offering a deeper commentary on the complexities of faith, morality, and the battle between good and evil in Indonesian culture. This research is useful for future research, such as analyzing other genres such as horror comedy, based on the Hank Davis and Javor theory. This is also helpful in cultural, literary, and film studies by showing how religious elements can be used in horror to create stories that are both locally relevant and universal.